Autonomous Warfare and Moral Dilemmas: An Islamic Ethical Analysis of AI Combatants - Muhammad Febri Eka Saputra; Dahyul Daipon (Program Studi Magister Hukum Islam - UIN Bukittinggi, 2026)
The militarization of Artificial Intelligence (AI) through autonomous weapons such as drones, killer robots, and cyberwarfare has sparked pressing ethical and legal debates globally. However, limited attention has been given to this issue within Islamic legal scholarship. This study aims to explore the ethical dilemmas posed by AI warfare—particularly regarding autonomy, moral agency, and the attribution of responsibility—through a multidisciplinary literature review grounded in Islamic jurisprudence (fiqh jināyah), the objectives of Islamic law (maqāṣid al-sharī‘ah), and principles of legal responsibility (taklīf and niyyah). The paper contrasts Islamic ethical reasoning with secular frameworks in technology ethics to address questions such as: Who bears the sin when an AI system kills? Can moral liability be assigned to a non-human agent? And can AI be utilized in legitimate jihād under Islamic rules of engagement? The study finds that while AI may assist military objectives, it lacks the intentionality (niyyah) and moral capacity required under Islamic law for justifiable violence, thus placing full accountability on human actors. This work contributes a novel Islamic legal-ethical framework to evaluate the permissibility and boundaries of AI warfare in modern conflict.